Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
[tex]\sf x=2+\sqrt{6},\:x=2-\sqrt{6}[/tex]
Explanation:
[tex]\sf y = x^2 -4x[/tex]
given that y = 2
[tex]\sf x^2 -4x = 2[/tex]
[tex]\sf x^2 -4x -2 = 0[/tex]
using quadratic formula:
[tex]\sf x = \dfrac{ -b \pm \sqrt{b^2 - 4ac}}{2a} \ \ \ when \ ax^2 + bx + c = 0[/tex]
[tex]\rightarrow \sf x_{1,\:2}=\dfrac{-\left(-4\right)\pm \sqrt{\left(-4\right)^2-4\cdot \:1\cdot \left(-2\right)}}{2\cdot \:1}[/tex]
[tex]\rightarrow \sf x_1=\dfrac{-\left(-4\right)+2\sqrt{6}}{2\cdot \:1},\:x_2=\dfrac{-\left(-4\right)-2\sqrt{6}}{2\cdot \:1}[/tex]
[tex]\rightarrow \sf x=2+\sqrt{6},\:x=2-\sqrt{6}[/tex]
in decimals:
[tex]\rightarrow \sf x=4.45 , \ -0.45[/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.